2009
DOI: 10.1002/pssb.200945146
|View full text |Cite
|
Sign up to set email alerts
|

Velocity, temperature, and normal force dependence on friction: An analytical and molecular dynamics study

Abstract: In this work we use a quasistatic Tomlinson model to propose an extension of the analytical one-dimensional model developed by Gnecco et al. [Phys. Rev. Lett. 84, 1172] and Sang et al. [Phys. Rev. Lett. 87, 174301 (2001)] to describe some aspects of friction. In our model we include the normal force and the dependence with the direction of movement of the object which is dragged over the surface. The angular dependence of the model is in agreement with the results of the FrenkelKontorova-Tomlinson model discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Therefore, the dynamic contact between two sliding solids has been widely studied both analytically and experimentally across various disciplines at the nano-and macroscale [1][2][3][4]. Nanoscale investigations over the last decade have shown that factors including the contact force [5][6][7][8][9][10], contact area [11][12][13][14][15], sliding velocity [7,8,10,[16][17][18][19], surface roughness [11], temperature [20,21], humidity [16,18,22], and wear [6,23] of the interface are important factors for dynamic friction. However, these effects are not well understood to date.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the dynamic contact between two sliding solids has been widely studied both analytically and experimentally across various disciplines at the nano-and macroscale [1][2][3][4]. Nanoscale investigations over the last decade have shown that factors including the contact force [5][6][7][8][9][10], contact area [11][12][13][14][15], sliding velocity [7,8,10,[16][17][18][19], surface roughness [11], temperature [20,21], humidity [16,18,22], and wear [6,23] of the interface are important factors for dynamic friction. However, these effects are not well understood to date.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the dynamic contact problem from analytical and experimental perspectives7891011 to elucidate influential factors, including the contact force121314151617, contact area18192021, sliding velocity14151722232425, surface roughness18, temperature2627, humidity222428, and interface wear1329. However, these effects are still not fully understood.…”
mentioning
confidence: 99%
“…For this reason, friction in this regime should be understood in much more details and several studies have been conducted to achieve such a scale. [2][3][4][5][6][7] Among these studies, the dependence of friction force on the normal load was most thoroughly investigated. In 1990, Hirano and Shinjo 8,9 proposed an atomistic model to describe the origin of the friction force between two clean solid surfaces in contact.…”
mentioning
confidence: 99%